2021
DOI: 10.1530/jme-20-0321
|View full text |Cite
|
Sign up to set email alerts
|

Neuritin inhibits astrogliosis to ameliorate diabetic cognitive dysfunction

Abstract: Earlier, it was shown that reversing the downregulation of neuritin expression in the brain improves central neuropathy in diabetic rats. We investigated the protective mechanism of neuritin in diabetic cognitive dysfunction via astrocytes. Further, the impact of the overexpression of neuritin in the cortex and the hippocampus on diabetic cognitive dysfunction and astrogliosis in type 2 diabetic (db/db) mice was assessed. Antagonists were used to inhibit the JAK2/STAT3 signaling pathway in U-118MG, an astrocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…The STAT3-dependent IL-17 production was further confirmed by the pretreatment of cells with a small molecule compound stattic, a selective STAT3 inhibitor that inhibits the activation, dimerization, and nuclear translocation of STAT3 by interacting with its SH2 domain ( 56 , 57 ) and represses STAT3 phosphorylation ( 58 ). In the current study, the pretreatment of PBMCs significantly repressed STAT3 phosphorylation at Tyr705 by cryptococcal stimulation in CD4 + T cells and further diminished the IL-17-producing CD4 + T cells and secretory IL-17 in the cell culture supernatant.…”
Section: Discussionmentioning
confidence: 95%
“…The STAT3-dependent IL-17 production was further confirmed by the pretreatment of cells with a small molecule compound stattic, a selective STAT3 inhibitor that inhibits the activation, dimerization, and nuclear translocation of STAT3 by interacting with its SH2 domain ( 56 , 57 ) and represses STAT3 phosphorylation ( 58 ). In the current study, the pretreatment of PBMCs significantly repressed STAT3 phosphorylation at Tyr705 by cryptococcal stimulation in CD4 + T cells and further diminished the IL-17-producing CD4 + T cells and secretory IL-17 in the cell culture supernatant.…”
Section: Discussionmentioning
confidence: 95%
“…In the central nervous system, this signaling pathway is closely related to brain in ammation and the survival and development of neurons/glial cells [41]. It has been found that JAK2 and STAT3 can regulate synaptic plasticity in hippocampus, which is closely related to learning and memory, and JAK2-STAT3 signaling pathway is involved in cognitive improvement [20][21][22][23].Therefore, more and more attention has been paid to the role of JAK2-STAT3 signaling pathway in central nervous system diseases, including Alzheimer's disease, depression and anxiety disorders. AG490 is a speci c antagonist of JAK2 and one of the PTK inhibitors [33].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also found that JAK2-STAT3 signaling pathway is involved in cognitive improvement [20][21][22][23], and JAK2-STAT3 signaling pathway is proposed to play a role in the activation of α 3 -, α 5 -and α 7 -nAChRs [24][25][26][27][28]. There seems a relationship between α 4 β 2 nAChRs and JAK2-STAT3 as well [29,30].…”
Section: Introductionmentioning
confidence: 99%